1994
DOI: 10.1007/bf02372358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some insect growth regulators on natural enemies of scale insects (Hom.: Coccoidea)

Abstract: We report and discuss effects of four insect growth regulators: buprofezin, fenoxycarb, pyriproxyfen and chlorfluazuron, at concentrations recommended for agricultural use on six species of natural enemies of homopteran pests.Dipping in buprofezin had no appreciable effect on adult mortality, oviposition and development of Comperiella bifasciata (Howard) (Hymenoptera : Encyrtidae). when exposed to hosts treated with buprofezin, percentage mortality of adult Encyrtus infelix Embleton (Encyrtidae) was low ; bupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 16 publications
(19 reference statements)
2
31
0
1
Order By: Relevance
“…However, Balasubramani and Regupathy (1994) reported no effect of buprofezin on larval stages of C. carnea. Pyriproxyfen suppressed adult emergence of Podisus maculiventris (Say) (Declercq et al, 1995) and egg hatch in Elatophilus hebraicus Pericart (Mendel et al, 1994). Pyriproxyfen exposure in the nymphal stage caused some deformities in adult G. punctipes, but not O. insidiosus (Say), and no effects on reproduction were observed for either species (Naranjo and Prabhaker, unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Balasubramani and Regupathy (1994) reported no effect of buprofezin on larval stages of C. carnea. Pyriproxyfen suppressed adult emergence of Podisus maculiventris (Say) (Declercq et al, 1995) and egg hatch in Elatophilus hebraicus Pericart (Mendel et al, 1994). Pyriproxyfen exposure in the nymphal stage caused some deformities in adult G. punctipes, but not O. insidiosus (Say), and no effects on reproduction were observed for either species (Naranjo and Prabhaker, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Buprofezin had no measurable effects on survival, molting or reproduction of G. punctipes or O. insidiosus (Naranjo and Prabhaker, unpublished). The most dramatic negative effects of these IGRs have been demonstrated for coccinellid beetles inhabiting perennial systems (Hattingh and Tate, 1995;Magagula and Samways, 2000;Mendel et al, 1994;Smith et al, 1999). Although coccinellids were rare at our study site, we observed no consistent negative effects of either IGR on these taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when the host parasitism rate was examined, no significant differences were found among all the agrochemicals tested, although copper oxychloride with a TC value of 2 could be seen as potentially slightly harmful. According to Mendel et al (1994), chlorfluazuron ingestion of Chilocorus bipustulatus adult females or dipping treatment of the eggs prevented emergence from the egg. Furthermore, in Diadegma semiclausum specimens that ingested chlorfluazuron, host parasitism was also significantly decreased (Haseeb et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…but not with parasitoid wasps of other pest species in citrus (Ishaaya et al 1992, Mendel et al 1994, Grafton-Cardwell et al 2006). There remains no clear evidence however, to pinpoint a cause for the change in pest status of M. gulosa thoughout its recorded history in southern California and the San Joaquin Valley.…”
Section: Marmara Gulosa In the San Joaquin Valley (Sjv) 1999 To Presentmentioning
confidence: 99%